2019
DOI: 10.1016/j.jinf.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of colonisation with carbapenem-resistant Enterobacteriaceae among patients admitted to Vietnamese hospitals: Risk factors and burden of disease

Abstract: http://creativecommons.org/licenses/by-nc-nd/4.0/ ) 116 D.M. Tran, M. Larsson and L. Olson et al. / Journal of Infection 79 (2019) 115-122 Conclusion: These data indicate that there is an epidemic spread of CRE in Vietnamese hospitals with rapid transmission to hospitalised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 33 publications
2
39
3
5
Order By: Relevance
“…A previous study from our hospital has reported a prevalence of 14.3% of VRE carriage among hospitalized patients, identified invasive devices and duration of antimicrobial treatment as risk factors, and found that VRE carriage was not an independent predictor of mortality (12). Similar studies from other regions have reported VRE carriage rates ranging from 2 to 37% (13-15), while prevalence rates for CRGN rectal carriage ranged from 5.3 to 52% (16)(17)(18). At the same time, there is an increased risk of carbapenem-resistant enterobacteriaceae (CRE) infection and mortality in patients who test positive for carriage of CRE (19,20).…”
Section: Introductionsupporting
confidence: 57%
“…A previous study from our hospital has reported a prevalence of 14.3% of VRE carriage among hospitalized patients, identified invasive devices and duration of antimicrobial treatment as risk factors, and found that VRE carriage was not an independent predictor of mortality (12). Similar studies from other regions have reported VRE carriage rates ranging from 2 to 37% (13-15), while prevalence rates for CRGN rectal carriage ranged from 5.3 to 52% (16)(17)(18). At the same time, there is an increased risk of carbapenem-resistant enterobacteriaceae (CRE) infection and mortality in patients who test positive for carriage of CRE (19,20).…”
Section: Introductionsupporting
confidence: 57%
“…Indeed, the acquirement of CRE infections is highly related to certain risk factors, such as: being transferred between hospitals or from long-term care centers; a long stay in the hospital, especially in an intensive care unit; having a surgical operation; transplantation; antibiotics usage; central venous catheter presence; having diabetes mellitus [ 35 , 36 ]. In this study, the majority of CRE isolates were from patients in the in the neonatal unit (40.3%), followed by the plastic surgical unit (14.1%), urology-gy-nephrology unit (11.1%), pediatric reanimation unit (13%), medical-surgical resuscitations (11.1%) and finally the medicine unit (10.1%).…”
Section: Discussionmentioning
confidence: 99%
“…The mcr-1 gene can be transmitted through the plasmid to colistin-sensitive strains. [33][34][35][36] Another concern is the emergence of colistin resistance during therapy among KPCproducing strains of P. aeruginosa in Switzerland, 37 USA, 38 and Australia. 8 As the main benefit of this study was to develop an HRMA assay to detect low levels KPC-producing, ESBL producing simultaneously, and CRPA strains, we next selected the KPC/IMP/mprA primer set1 and TEM/ SHV/mcr-1 primers set2 combination for a multiplex assay assessment.…”
Section: Dovepressmentioning
confidence: 99%